Representation of a Consumptive Lifestyle in Tokopedia Ads "Tampil Cantik Sekali Klik" - Triana Qotrun Nada; Filosa Gita Sukmono (Jogjakarta Communication Conference (JCC), 2023)
This study describes the formation of a consumptive lifestyle and the emergence of a culture of consumerism towards Tokopedia's "Tampil Cantik Sekali Klik" advertisement. The consumptive lifestyle begins with a consumption process that is not relaxing and has an impact on people's behavior that cannot distinguish between primary needs and mere desires. Tokopedia is an e-commerce in Indonesia that provides all your daily needs with various features. Many conveniences are present because of e-commerce such as Tokopedia. This convenience then attracts many users to shop more often through Tokopedia. As a result, their consumption process changes, from fulfilling needs to fulfilling wants. This study uses descriptive qualitative research with Roland Barthes' Semiotic research method. Barthes with his theory focuses on connotation, denotation, and mythology. The results of his research are, through the meaning of denotations, connotations and myths by Roland Barthes, it is revealed that what Tokopedia displays in its advertisements can trigger a consumptive lifestyle for its users. The consumptive lifestyle arises due to the convenience offered by Tokopedia's "Tampil Cantik Sekali Klik" advertisement, making people unable to distinguish between their main needs and desires. This convenience is packaged in the features provided by Tokopedia through the advertisements they display.